Violence in act and the violentlike (1993)
Starting from a critical reappraisal of Freud's Group Psychology  and Analysis of the Ego, this paper establishes the differences between masses and society on the one hand, and between bond and relation on the other, key notions for understanding violence. In this regard, attention is drawn to the  comprehension of the thanatical, as well as the libidinal, as a factor of binding. Conceptual differences are also established between violence in act and the violentlike, not restricted to the opposition between individual and society, or masculine and femenine, poles which, nevertheless, are also taken into account. Based on these fundamental references, this paper considers violence as a "radical imbalance of powers", and the example is given of a case directly related to our present situation: the hired killer.